2018
DOI: 10.1021/acs.jchemed.8b00387
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of First-Semester Organic Chemistry Peer-Led Team Learning and Cyber Peer-Led Team Learning Students’ Use and Explanation of Electron-Pushing Formalism

Abstract: The purpose of this parallel convergent mixed methods study was to characterize organic chemistry students’ expression of electron-pushing formalism skills who had participated in peer-led team learning (PLTL) and cyber peer-led team learning (cPLTL), a synchronous online version of peer-led team learning (PLTL) workshops. A new electron-pushing formalism analytic framework was developed from a review of the literature in addition to analysis of students’ interview artifacts, using a constant-comparison proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…Peer leaders who adopt a facilitator approach to their interactions with students were more likely to acknowledge, build upon, and elaborate ideas as opposed to a more instructional based approach lend to students working individually when not listening to the peer leader, be answer-focused, and unequally participate (Brown, Sawyer, Frey, Luesse, & Gealy, 2010). Integrating active collaboration was found to be a potentially crucial element as it was discovered that organic chemistry students that participated in cyber PLTL (a synchronous online version of PLTL) had significantly less success drawing the correct predicted product of a chemical reaction (Wilson & Varma-Nelson, 2018). Facilitating collaborations is necessary to catalyze social constructivist learning experiences.…”
Section: Peer-led Team Learning (Pltl)mentioning
confidence: 99%
“…Peer leaders who adopt a facilitator approach to their interactions with students were more likely to acknowledge, build upon, and elaborate ideas as opposed to a more instructional based approach lend to students working individually when not listening to the peer leader, be answer-focused, and unequally participate (Brown, Sawyer, Frey, Luesse, & Gealy, 2010). Integrating active collaboration was found to be a potentially crucial element as it was discovered that organic chemistry students that participated in cyber PLTL (a synchronous online version of PLTL) had significantly less success drawing the correct predicted product of a chemical reaction (Wilson & Varma-Nelson, 2018). Facilitating collaborations is necessary to catalyze social constructivist learning experiences.…”
Section: Peer-led Team Learning (Pltl)mentioning
confidence: 99%
“…This shows that both electron-pushing formalisms and electron-pushing techniques were an explanatory and a predictive method for mechanistic thinking about what happen during reaction mechanisms. Wilson and Varma-Nelson (2018) reported that electron-pushing formalisms were rooted in a paper written by Kermack and Robinson (1922), that described the electrons move from a high electron density to a low-density area within the covalent bond.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to concerns about academic dishonesty being a driver of perceived positive effects in online classes . Previous studies of online chemistry classes show that a lack of interactivity can cause poor performance on instrumental learning tasks . The implication of these results is the need for students to interact with instructors and peers.…”
Section: Introduction and Contextmentioning
confidence: 99%
“…6 Previous studies of online chemistry classes show that a lack of interactivity can cause poor performance on instrumental learning tasks. 7 The implication of these results is the need for students to interact with instructors and peers. Unlike traditional classrooms, where feelings of belonging arise from close proximity, in online courses interactions must be carefully curated.…”
Section: ■ Introduction and Contextmentioning
confidence: 99%